Interactions and Cytotoxicity of Human Neurodegeneration- Associated Proteins Tau and α-Synuclein in the Simple Model Dictyostelium discoideum - Mroczek, Katelyn; Fernando, Sanjanie; Fisher, Paul R.; Annesley, Sarah J. (Frontiers in Cell and Developmental Biology, 2021)
The abnormal accumulation of the tau protein into aggregates is a hallmark in neurodegenerative diseases collectively known as tauopathies. In normal conditions, tau binds off and on microtubules aiding in their assembly and stability dependent on the phosphorylation state of the protein. In disease-affected neurons, hyperphosphorylation leads to the accumulation of the tau protein into aggregates, mainly neurofibrillary tangles (NFT) which have been seen to colocalise with other protein aggregates in neurodegeneration. One such protein is α-synuclein, the main constituent of Lewy bodies (LB), a hallmark of Parkinson’s disease (PD). In many neurodegenerative diseases, including PD, the colocalisation of tau and α-synuclein has been observed, suggesting possible interactions between the two proteins. To explore the cytotoxicity and interactions between these two proteins, we expressed full length human tau and α-synuclein in Dictyostelium discoideum alone, and in combination. We show that tau is phosphorylated in D. discoideum and colocalises closely (within 40 nm) with tubulin throughout the cytoplasm of the cell as well as with α-synuclein at the cortex. Expressing wild type α-synuclein alone caused inhibited growth on bacterial lawns, phagocytosis and intracellular Legionella proliferation rates, but activated mitochondrial respiration and non-mitochondrial oxygen consumption. The expression of tau alone impaired multicellular morphogenesis, axenic growth and phototaxis, while enhancing intracellular Legionella proliferation. Direct respirometric assays showed that tau impairs mitochondrial ATP synthesis and increased the “proton leak,” while having no impact on respiratory complex I or II function. In most cases depending on the phenotype, the coexpression of tau and α-synuclein exacerbated (phototaxis, fruiting body morphology), or reversed (phagocytosis, growth on plates, mitochondrial respiratory function, Legionella proliferation) the defects caused by either tau or α-synuclein expressed individually. Proteomics data revealed distinct patterns of dysregulation in strains ectopically expressing tau or α-synuclein or both, but down regulation of expression of cytoskeletal proteins was apparent in all three groups and most evident in the strain expressing both proteins. These results indicate that tau and α-synuclein exhibit different but overlapping patterns of intracellular localisation, that they individually exert distinct but overlapping patterns of cytotoxic effects and that they interact, probably physically in the cell cortex as well as directly or indirectly in affecting some phenotypes. The results show the efficacy of using D. discoideum as a model to study the interaction of proteins involved in neurodegeneration.